LAFAMS: Account management system for Malaysian small legal firms - Zuhairah Ariff, Abd Ghadas; Azim Zaliha, Abd Aziz; Mariana, Jusop (Universiti Putra Malaysia, 2015)
One of the vital components of a successful private legal practice is good account management. Legal firms have a unique business process and specific rules on how accounting records should be kept and recorded. At present, there are many software packages for legal account management systems such as the MyCase web-based legal practice management software and the QuickBooks legal accounting software. However, for small- and medium-size legal firms in Malaysia, the software designed for international use might not be suitable. The majority of local law firms are SMEs and most of the time, their account management is done by the lawyers themselves. With limited knowledge of accounting and business management, it is not a surprise that many legal practitioners face difficulties in managing their accounts. LAFAMS (Law Firm Account Management System) was developed to assist legal firms to manage their financial transactions, monitor their performance, record cash inflow and outflow and facilitate the auditing process. The system requires only the basic Windows operating system and is easy to operate. The report produced by LAFAMS should be sufficient for submission to the Bar Council as evidence of proper account-keeping by legal firms.